Bridging intensity is associated with impaired hematopoietic recovery after BCMA CAR-T therapy for multiple myeloma - Frenking, Jan; Zhou, Xiang; Rejeski, Kai; Wagner, Vivien; Costello, Patrick; Hielscher, Thomas; Gatti, Lilan; Kauer, Joseph; Nadeem, Omar; Mai, Elias K.; Michel, Christian S.; Friedrich, Mirco; et al. (Blood advances, 2025)
Chimeric antigen receptor (CAR) T-cell (CAR-T) therapy represents a major advance in the treatment of relapsed/refractory multiple myeloma (RRMM). However, the long time span from leukapheresis to actual CAR-T infusion often necessitates bridging therapies. Because of limited knowledge about the effects of bridging on post-CAR-T clinical course and outcomes, the selection of treatment options is challenging. In this multicenter international observational study, we explored the impact of bridging therapy on hematopoietic reconstitution in 158 patients with RRMM treated with B-cell maturation antigen (BCMA)-directed CAR-T therapy. Based on exposure to classical cytotoxic (CTX) chemotherapy, we classified bridging regimens as non-CTX, intermediate CTX (1-2 CTX agents), or intensive CTX (≥3 CTX agents or high-dose therapy with stem cell transplantation). We found associations between the number of CTX agents used and impaired post-CAR-T hematopoietic reconstitution, evident across hematopoietic cell lineages and particularly manifesting during the late post-CAR-T period. Intensive CTX bridging was associated with a prolonged time to neutrophil and platelet recovery, distinct patterns of hematopoietic recovery (eg, an intermittent phenotype characterized by a second drop), an increased susceptibility to severe infections and a significantly increased risk for severe late cytopenias in univariate and multivariate models. Taken together, these results highlight that bridging intensity distinctly shapes the trajectory of hematopoietic recovery after BCMA CAR-T therapy. Targeted and novel immunotherapies could provide alternatives for bridging, and high-risk patients may particularly benefit from enhanced monitoring, prophylaxis, and supportive care.